2018
DOI: 10.1111/modl.12512
|View full text |Cite
|
Sign up to set email alerts
|

Pronunciation Instruction Can Improve L2 Learners’ Bottom‐Up Processing for Listening

Abstract: Listening is widely regarded as an important skill that is difficult and necessary to teach in L2 classrooms. Listening requires both top‐down and bottom‐up processing, yet pedagogical techniques for the latter are often lacking. This study explores the efficacy of pronunciation instruction (PI) for improving learners’ bottom‐up processing. The study recruited 116 relatively novice learners of Spanish as a foreign language and provided the experimental groups with brief lessons in PI emphasizing segmental or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 46 publications
1
35
0
1
Order By: Relevance
“…How widespread is the analysis of ordinal data with metric methods in bilingualism research? Although there are examples of the application of appropriate methods (e.g., Kissling, 2018;Tare et al, 2018), this is far from common. We quantified this tendency by searching for all articles published in Bilingualism: Language and Cognition in 2019-2020, containing the words 'rating' or related words.…”
Section: A Pervasive Problem In Bilingualismmentioning
confidence: 99%
See 1 more Smart Citation
“…How widespread is the analysis of ordinal data with metric methods in bilingualism research? Although there are examples of the application of appropriate methods (e.g., Kissling, 2018;Tare et al, 2018), this is far from common. We quantified this tendency by searching for all articles published in Bilingualism: Language and Cognition in 2019-2020, containing the words 'rating' or related words.…”
Section: A Pervasive Problem In Bilingualismmentioning
confidence: 99%
“…In the case of many response categories, complexity may be reduced by plotting only a subset of interest or by averaging the predictions for several categories(Kissling, 2018).…”
mentioning
confidence: 99%
“…Yläkoulussa mukaan tulee kaikkien vieraiden kielten oppimäärissä myös kirjoittaminen: "Harjoitellaan tunnistamaan opiskeltavan kielen foneettisen tarkekirjoituksen merkkejä sekä tuottamaan tarvittavia kirjoitusmerkkejä." Tutkimuksissa on havaittu, että yleisen fonologisen tietoisuuden määrä korreloi ääntämisen ymmärrettävyyden kanssa (Venkatagiri & Levis, 2007) ja erityisesti kohdekielen prosodian opettamisen on havaittu helpottavan vieraan kielen ymmärtämistä (Kissling, 2018). Lisäksi Lintunen (2004) on havainnut foneettisen kirjoituksen osaamisen ja ääntämisen välisen yhteyden.…”
Section: Eksplisiittinen ääNtämisen Opetusunclassified
“…Mounting evidence from research suggests that pronunciation instruction is able to improve learners’ speaking skills (Derwing and Munro, 2015; Derwing et al, 1998; Levis, 2018) and plays a central role in improving their intelligibility, comprehensibility, and accuracy. Pronunciation instruction can also help with other skill areas such as listening (Kissling, 2018), as well as reading and writing (Darcy, 2018; Levis, 2018: 190). Recently a meta-analysis of pronunciation studies by Lee et al (2015) examined a large number of experimental studies and observed that many report improvements in pronunciation accuracy as a result of pronunciation instruction (e.g.…”
Section: Introductionmentioning
confidence: 99%